Editor-in-Chief Note - Lee, Hannah (Consilience, 2009)
Dear Readers, I am often asked to define sustainable development and its broad relevance today. The most widely used definition is surely the Brundtland Commission’s: that which meets the needs of the present without compromising the ability of future generations to meet their own needs. With this second issue ofConsilience: The Journal of Sustainable Development, I am eager to share with you the view that I wholeheartedly support and credit to Ismail Serageldin, the Director of the Library of Alexandria in Egypt and author of dozens of academic essays on sustainability: sustainable development as the sustainability of opportunity. Sustainability, he argues, is giving future generations as many opportunities as, if not more than, we have had ourselves. In this second issue of Consilience the authors translate this “giving” to the growth of opportunity: economic opportunity, knowledge transfer, and natural conservation. In this second issue of Consilience, the editors and writers worked ambitiously to create and inspire interdisciplinary dialogue between students and development practitioners that would promote this sustainability of opportunity. We hope to provide a glimpse into the pool of exceptional motivation of our authors, who are each committed to share their interests and experiences with you. Our vision: to reveal clearly the aspirations and voices of the authors, and to share the reasoning and discussion behind the competitive selection process for articles for Consilience. To support this vision each article in this Issue features two additional notes, as introductions to the fascinating topics and multi-disciplinarity behind each piece: The Senior Editor’s Note, found before each piece and the Author’s Note, the authors’ own preface to readers. In so doing, we hope to expand the dialogue on issues of sustainable development. Here, I briefly introduce to you the authors and their written work published in Issue II of Consilience. These authors are students and professors of health, economics, social psychology, epidemiology, political science, transitional justice, Asian studies, and pastoral development. Like many of our readers, they are also development practitioners, who work at field study schools, research universities and with governmental agencies around the world. In reading their written work, you will encounter an immense diversity of research methods used, including the Likert Scale, a psychometric scale for evaluating survey responses, and Multivariate General Linear model analyses, for identifying the regression and variance of collected data. In the “Author’s Notes,” the contributors describe their motivations for and research experiences from schools around the world, including Tanzania, Ghana, Togo, Brazil, and parts of Asia. Their innovative thinking is clear when you read of their suggested tools for development and recommended solutions in Maher Abu-Madi and Rashed Al-Sa’ed’s “Towards Sustainable Wastewater Reuse in the Middle East and North Africa” and Richard King’s “The Political Economy of the Resource Curse in Gabon: Lessons for Ghana.” I invite you to relate to their experiences as expressed through distinct voices, organized into the four categories of Consilience: scholarly articles, field notes, photo essays, and opinion pieces. In the scholarly articles, the authors present case studies that respond to the ideas of eminent thinkers in economics, history of the environment, the labor movement, and gender equality: Amartya Sen, Ravi Kanbur, Ester Boserup, and Elizabeth Economy. I welcome you to follow five authors as they investigate community-based watershed management in the Philippines (“Evaluation of the NZAID project” by Freeman et al.), and four others as they conduct 123 surveys in three villages over the course of four days, in the northern Shaanxi province in China (“Social Responses to Environmental Degradation in Northwest Rural China” by Moore et al.). The field notes, photo essays, and opinion pieces are dually captivating personal transcripts and critical examinations of current development work. I was personally moved by the description of child labor issues in Schapper’s “From the Global to the Local: How International Child Rights in Bangladesh Reach the Grass Roots’ Level.” Cumming’s “Communicable Disease Surveillance and Response in Uganda,” which describes his work with Village Health Teams and the National Task Force on Cholera and Hepatitis E. in Kampala, Uganda presents a novel perspective on issues of global health. Burgess’ “Illusions of Grandeur: The Role of the Psychosocial in a Sennian Approach to Escaping Urban Poverty” examines the psychosocial barriers to poverty alleviation projects in Brazilian shantytowns in a thought-provoking and critical manner. In Issue II’s four photo galleries, you will read about what inspired photo essayist Bachhuber to chronicle India’s most famous and toxic river, the Ganges. Batkhsihig affords us a behind-the-scenes tour of the daily tasks of Mongolian herder families. Laso will expose you to the hidden aquatic lifestyle and vast seasonal migration areas of the Podocnemis, the river turtle of the Amazonian landscape, and Drs. Nyasimi and Okang’a of the Millennium Villages Project will introduce you to the Sauri Village’s new community ambulance and community-founded theater group. To return to our understanding of sustainable development as thesustainability of opportunity, it is my hope that you will join us in commenting on each piece through this provided online medium and encouraging the growth of vast opportunities: in research methods, for actors involved in drafting policies, and in academic dialogue. We know that the opportunities must continue to grow in the context of real-world poverty alleviation projects, legislation for environmental governance, and provisions beyond basic needs. Thank you for your interest in Issue II of Consilience: The Journal of Sustainable Development. I welcome you to contribute, through comments and critique, and as future writers. With regards, Hannah Lee Editor-in-Chief Consilience: The Journal of Sustainable Development